Eurycoma longifolia root aqueous extract augments the testosterone level and spermatogenesis in adult male rats - Mohammed Al-Faqeh, Hamoud Hussein; Mustafa Mahmoud, Mohammed Imad Al-Deen (IIUM Journal Publication Unit, 2019)
Introduction The Eurycoma longifolia (EL) root aqueous extract has long been used as an enhancer of male sexual performance. However, data from previous studies in both human males and experimental male animals on the testosterone level in those given the EL extract orally were at best insufficiently conclusive. Materials and Method Sixty-four healthy adult male Sprague Dawley rats were acclimatized, and randomized into six test groups and one control group. All rats where given either the aqueous EL extract or distilled water via metal gavage needle. The first three test groups received the low (50mg/kg bw), medium (100mg/ kg bw) and high (200mg/kg bw) doses respectively of the EL daily for 15 days only. The second three test groups continued receiving the same daily treatment doses for 30 days. The controls were given distilled water only. At the end of each of the study period, blood samples were collected via cardiac puncture and the rats were euthanized. The testicles were obtained, weighed, and processed for histological examination. Results The sera testosterone levels were higher in animals which received the medium and high doses for both treatment duration. Rats which received medium and high oral doses of EL showed an increase of spermatogenesis and mature spermatozoa. Conclusion The optimal enhancing effect on sera testosterone levels and testicular spermatogenesis of EL treatment in adult male rats was observed with the medium dose of 100mg/kg bw given once daily for both 15 and 30 days.